Food safety practice and associated factors among food handlers working in food and drinking establishments in Finote Selam, in resource-limited settings - Abraham Teym; Balew Adane; Bayou Tilahun Assaye; Tirsit Ketsela Zeleke (Frontiers in Sustainable Food Systems)
BackgroundFood safety is a major public health concern, with 10%−20% of foodborne disease outbreaks linked to contamination by food handlers. The problem is especially severe in developing countries like Ethiopia, mainly due to poor sanitation and improper food handling.ObjectivesTo assess food safety practices and associated factors among food handlers working in food and drinking establishments in Finote Selam, in Resource-Limited Settings.MethodsA community-based cross-sectional study was conducted from February 20 to March 20, 2024 involving 412 randomly selected food handlers in Finote Selam, Ethiopia. Data were collected via a structured questionnaire and analyzed using SPSS version 26. Descriptive statistics summarized socio-demographic data, while bivariate and multivariable logistic regression identified associated factors. Variables with p < 0.25 in bivariate analysis were included in the multivariable model. Results were reported using adjusted odds ratios (AOR) with 95% confidence intervals, and significance was set at p ≤ 0.05.ResultsA total of 412 food handlers participated in the study, with 51.6% revealing poor food safety practices. Significant factors associated with poor practices included lack of food safety training (AOR = 3.721; 95% CI: 1.380–8.982), limited work experience (AOR = 3.050; 95% CI: 1.873–4.986), lack of regular supervision (AOR = 1.653; 95% CI: 1.108–2.538), and inadequate food safety knowledge (AOR = 1.25; 95% CI: 1.082–2.934).ConclusionThe present study revealed poor food handling practices among food handlers. The main factors associated with these poor practices were lack of food safety training, limited work experience, insufficient supervision, and inadequate food safety knowledge. Food handlers should receive regular training on food hygiene and safety to improve their knowledge and practices. Additionally, routine sanitary inspections of food and drink establishments are recommended.